Future of health technology - Bushko, Renata Glowacka (Studies in health technology and informatics, 2002)
This text provides a comprehensive vision of the future of health technology by looking at the ways to advance medical technologies, health information infrastructure and intellectual leadership. It also explores technology creations, adoption processes and the impact of evolving technologies.